PELATIHAH DASAR PENGGUNAAN APLIKASI MICROSOFT OFFICE DI MTS INSAN KREASI - Thoyyibah Thoyyibah; Tomi Hardi; Tita Puspitasari (Intimas, 2023)
Microsoft Word socialization is a word processing activity using the Windows operating system which is reliable enough to provide convenience for users. Besides being easy to operate, the variations and styles of letters use a full graphic model. In Microsoft Word, the use of commands is usually more than one. You can do this through the menus and toolbars in application programs or via the mouse and keyboard. Microsoft Word is one of the members of Microsoft Office that is often used in terms of the most sophisticated word processing today. The current use of Microsoft Word is only part of the functions that are used, there are still many that have not been used optimally. Many people who type only by relying on the ability of their fingers actually Microsoft Word already provides features that can make us even faster in typing. The results of this socialization add knowledge and a spirit of independence to the rest and female students. It is hoped that the knowledge gained at Community Service this time will be able to provide new enthusiasm for us in sharing knowledge and motivation and contributing to the younger generation, both within the community and family.